2012
DOI: 10.1590/s2179-64912012000100007
|View full text |Cite
|
Sign up to set email alerts
|

O uso de um software na (re)habilitação de crianças com deficiência auditiva

Abstract: The auditory training using the SARDA was effective, providing improvement of the speech perception ability, both in quiet and in noise, for the hearing impaired children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
0
8
0
12
Order By: Relevance
“…The efficiency of using a computer program in the (re)habilitation of hearing impaired child, user of hearing aids or cochlear implants, was shown in a research 9 , with an improvement in speech perception in quiet and in noise. The researchers verified that these children needed more time to do the activities, especially those ones which involved non-verbal and verbal sounds directly related to sustained attention 18 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of using a computer program in the (re)habilitation of hearing impaired child, user of hearing aids or cochlear implants, was shown in a research 9 , with an improvement in speech perception in quiet and in noise. The researchers verified that these children needed more time to do the activities, especially those ones which involved non-verbal and verbal sounds directly related to sustained attention 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Some authors 7,[9][10][11] report that the use of computers in therapeutic environment provides the child contact with computerization, enabling access to multiple strategies that enhance global and auditory development. In order to obtain the successful treatment of the patient, it is important to encourage him, as well as highlighting his correct answers during therapy, thus characterizing them as motivational sections 11 , as musical training and playing video games that allow a new learning of the subject 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a limitation of the therapeutic intervention studies, due to the loss of subjects during the therapeutic process. Another research has shown improvement in the ability of the figure-background in the post-CBAT assessment (4) , noticing a better performance on speech perception, both in acoustic environment unfavorable (that requires more of the figure-background skill from subject for understanding), as in a quiet environment (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the effects of the Computer-Based Auditory Training (CBAT) in different populations: people with hearing loss (1)(2)(3) , people with normal hearing and Central Auditory Processing Disorder (CAPD) (4,5) , people with normal hearing, auditory processing disorder and language (6,7) or speech disorder (5,8) , and others.…”
Section: Introductionmentioning
confidence: 99%